Hydroxyapatite/titania nanocomposites derived by combining high-energy ball milling with spark plasma sintering processes - Yu, L. G. (2012)
Hydroxyapatite-reinforced nanocomposites with titania nanocrystals addition are prepared by a homogeneous mixing of hydroxyapatite nanoparticles and titania nanocrystals based on high-energy ball milling and spark plasma sintering processes. The microstructural and mechanical properties of the HA/titania composites are studied by X-ray diffractometry analysis, Raman spectrometry, and scanning electron microscopy. The hardness and Young's modulus of the composites are characterized by a nanoindenter and they show that the incorporation of the titania nanocrystals improves the mechanical properties of the composites obviously and the improvement should be ascribed to the main solitary effect of the ceramic as additives as well as a denser composites due to combining high-energy ball milling with spark plasma sintering techniques. The bioactivity of the HA/titania composites is evaluated by immersing the spark plasma sintering (SPS) compact disk in the simulated body fluid (SBF) and the results indicate that the bioactivity of the composites is related to the addition of titania by inducing apatite nucleation on the sample's surface after being immersed in SBF.